Numerical Simulation of the Melting and Solidification Processes of Two Organic Phase Change Materials in Spherical Enclosures for Cold Thermal Energy Storage Applications - Vasco-Calle, D; Jonathan Jesus-Cofre, T (Elsevier Ltd, 2022)
The encapsulation of phase change materials (PCMs) is a convenient alternative for latent heat thermal energy storage systems (LHTESSs) because of the excellent relationship between their storage volume and the heat transfer surface. The goal is to establish a unified heat transfer behavior of encapsulated PCM. Computational fluid dynamics (CFD) numerical simulations are performed with ANSYS/Fluent of the melting and solidification processes of the commercial organic PCMs RT5HC and RT10HC. The numerical study involve a parametric study of the sphere diameter (40, 60, and 80 mm), thermal gradient (difference between wall temperature and phase change temperature) for melting (1–5 °C), and thermal gradient for solidification (1–3 °C). The numerical simulations implemented the experimentally obtained and temperature-dependent thermophysical properties of thermal conductivity (k), phase change enthalpy (L), specific heat (cp), and viscosity (μ) of the PCMs. The computational simulations allowed us to determine the behavior of the heat transfer coefficient (h) as a function of the liquid fraction (φ) and solid fraction (φso) of the PCM. Furthermore, nonlinear regression adjustments to the Nusselt number (Nu) curves allowed the fitting of power-law curves with suitable correlation parameters. Finally, the coefficients (a, b, and c) of the proposed fitting power-law curves were plotted and adjusted via linear regression through the origin as a function of the dimensionless numbers of Archimedes (Ar), Stefan (Ste), Grashof (Gr), Prandtl (Pr), and dimensionless thermal conductivity (κ), unifying the behavior of the melting and solidification processes through two correlations of the Nu number. These correlations will be helpful in the design of LHTESS tanks for their application in heat-pump-type air-conditioning systems in buildings. © 2022 Elsevier Ltd